2012
DOI: 10.1002/ana.23589
|View full text |Cite
|
Sign up to set email alerts
|

Real time quaking‐induced conversion analysis of cerebrospinal fluid in sporadic Creutzfeldt–Jakob disease

Abstract: Objective: Current cerebrospinal fluid (CSF) tests for sporadic Creutzfeldt–Jakob disease (sCJD) are based on the detection of surrogate markers of neuronal damage such as CSF 14‐3‐3, which are not specific for sCJD. A number of prion protein conversion assays have been developed, including real time quaking‐induced conversion (RT‐QuIC). The objective of this study is to investigate whether CSF RT‐QuIC analysis could be used as a diagnostic test in sCJD. Methods: An exploratory study was undertaken that analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
260
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 323 publications
(292 citation statements)
references
References 20 publications
12
260
2
8
Order By: Relevance
“…Most laboratories used either a BMG LABTECH Optima or a BMG LABTECH Omega, whereas 1 laboratory used a Tecan Infinite F200PRO (Tecan Group, Männedorf, Switzerland). Nine laboratories used hamster full‐length (23–231) rPrP (supplied by Bristol Institute of Blood Sciences, Bristol, UK),8, 9 2 used human full‐length (23–231) rPrP (produced in‐house),7 and 1 used a hamster–sheep chimeric rPrP (hamster 14–126 residues followed by sheep residues 141‐234, produced according to previously reported conditions) 5…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most laboratories used either a BMG LABTECH Optima or a BMG LABTECH Omega, whereas 1 laboratory used a Tecan Infinite F200PRO (Tecan Group, Männedorf, Switzerland). Nine laboratories used hamster full‐length (23–231) rPrP (supplied by Bristol Institute of Blood Sciences, Bristol, UK),8, 9 2 used human full‐length (23–231) rPrP (produced in‐house),7 and 1 used a hamster–sheep chimeric rPrP (hamster 14–126 residues followed by sheep residues 141‐234, produced according to previously reported conditions) 5…”
Section: Methodsmentioning
confidence: 99%
“…Shaking performed in a Thermomixer Comfort (Eppendorf, Hamburg, Germany) before being read in an Optima instrument.CSF = cerebrospinal fluid; Ham FL = hamster full‐length PrP (23–231)8, 9; Ham‐Sh chimeric = hamster residues 14–128 :sheep 141–234 5; Hum FL = human full‐length (23–231)—codon 129M6; PrP = prion protein; rfu = relative fluorescence units.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is much discussion in current literature as to whether the alpha‐synucleinopathies are actually prion‐like diseases 11. A recently described technique called real‐time quaking‐induced conversion (RT‐QuIC), which exploits the ability of prion protein to induce self‐aggregation, has been used to develop a diagnostic CSF test for sporadic Creutzfeldt–Jakob disease (sCJD), the most common human form of TSE 12. Using our expertize in RT‐QuIC,12 we have developed and tested a similar assay for the detection of a‐syn in CSF.…”
Section: Introductionmentioning
confidence: 99%
“…However, ongoing validation studies have demonstrated that the outcomes of RT-QuIC reactions depend on the exact conditions employed (biochemical, chemical and physical), as well as the nature of the sample and recombinant substrate. The protocol under evaluation by the National Microbiology Laboratory has been tested extensively for the detection of sporadic CJD (10,11,15,16 ). Using this protocol the Prion Laboratory Section achieved 100% sensitivity and 100% specificity in the evaluation of an external sporadic CJD infected CSF proficiency panel.…”
Section: Summary Of Test Resultsmentioning
confidence: 99%